Implant comparisons for grazing yearling steers - S. Laudert; L. Corah; R. Nelson; C. Sauerwein (Kansas Agricultural Experiment Station Research Reports, 1985)
Three field trials were conducted with grazing yearling steers to compare Compudose® and Ralgro® implants. Compudose® and Ralgro® implants. Compudose®-implanted steers gained faster (P<.05) than controls. Ralgro® improved daily gain by 3.8%. No significant difference was found between implants.
Keywords: Cattlemen& #x27; s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Grazing; Steers; Implants